An online electronic journal for teaching purposes - Jack Meadows; Fytton Rowland; Penny Yates-Mercer (Association for Learning Technology, 1997)
Electronic channels are rapidly taking off as a means of accessing journal literature (Lancaster, 1995). Behind the interest lies the increasing concern of academic libraries with the mounting cost of purchasing printed journals. Some commentators believe that higher-education institutions themselves will move into the electronic publishing field in order to control expenditure on journals (Okerson and O'Donnell, 1995). This rapid growth in the number of electronic journals available raises the immediate question - how will all those concerned with journals, as authors, editors, or readers, be trained? The prime purpose of the project described here is to explore the problems of providing such training. It was also planned that student feedback would assist the construction of an online teaching package.